DEVELOPMENT OF LIFE SKILLS THROUGH CALLIGRAPHY DESIGN AT PSKQ 4 YOGYAKARTA - Salsabilla, Imelia; Albin Jaya, Arim Irsyadulloh (AGUSPATI RESEARCH INSTITUTA, 2024)
This research aims to investigate the ability of students or students through calligraphy design in the PSKQ 4 Yogyakarta Islamic boarding school. Calligraphy training in guiding students to improve their abilities to the championship stage. The case study was carried out to gain in-depth insight into how calligraphy in various aspects of the educational art at the institution and can produce a global generation of calligraphers. The research method used involves participatory observation and interviews. The results of the study show that the PSKQ 4 Yogyakarta Islamic boarding school has implemented various calligraphy training solutions in time management, including the application of student training with different times, it is hoped that it can be carried out from the easiest to the most difficult level, and is encouraged to continue to work to get used to it. Although facing several obstacles such as the application of calligraphy training to students because a person's personality in grasping the material given is not all quick to respond. This study contributes to the education management literature by presenting concrete findings on the application of calligraphy art training in the context of Islamic education in Indonesia. The practical implications of the results of this study can be a reference for other Islamic educational institutions to improve their time management through calligraphers who are already qualified in this field.